A nurse‐led intervention improves detection and management of AKI in Malawi. Issue 4 (5th September 2016) - Kirwan, Christopher J.; Wright, Kelly; Banda, Peter; Chick, Aylwin; Mtekateka, Mwayi; Banda, Enos; Kawale, Zuze; Evans, Rhys; Dobbie, Hamish; Dreyer, Gavin
SUMMARY: Background: Acute kidney injury is common and has significant impact on mortality and morbidity. There is a global drive to improve the lack of knowledge and understanding surrounding the recognition, diagnosis and management of patients with AKI in resource poor healthcare systems. Objectives: We propose a nurse‐led education programme to medical and nursing staff of the Queen Elizabeth Central Hospital (QECH) in Blantyre, Malawi, will improve the overall care and understanding of patients with AKI that will still be effective 3 months later. Methods: This was a three phase, prospective interventional pilot study which evaluated base line knowledge and clinical practice amongst healthcare workers, provided a comprehensive combination nurse‐led class room and ward based teaching programme and evaluated the change in knowledge and clinical management of patients in the high dependency areas of the hospital immediately, and 3 months, after the teaching intervention. Results: The nurse‐led intervention significantly improved the healthcare workers attitudes towards detecting or managing patients with suspected AKI (p < 0.0001). There were also significant improvements in the completion of fluid charts and recording of urine output (p < 0.0001), corner stones of AKI management. Knowledge and clinical intervention was still present three months later. There was however little change in the understanding that AKI could be a significant clinical problem in QECH and that it may have a major impact on mortality and working practice and this needs to be addressed in future teaching programmes. Conclusions: A low cost, nurse‐led AKI educational intervention improved the knowledge and management of AKI at QECH, which was still evident 3 months later.